Resection and descent of rectal-sigmoid cancer at 77 years of age, with eutaxic, organic and functional reestablishment - Palma, Eduardo; Florio, José L.; Falconi, Luis; Nuchowich, Manuel; Castilla, Máximo; Rico Pena, Roberto (Cirugía del Uruguay, 1982)
One case of ulcerative-iniltrative rectosimoid cancer at the age of 77 is presened. Oncological radical treament was done through an abdominal approach, wih rectsimoid resection, lowering of the colon nd conservaion of he anal canal. Treament was performed at different steps: a- simultaneous previous double ostomy: ilesostomy and sphincer and cecolostomy; b- rectosigmoid widened resection and lowering of he colon; c- closure of the double ostomy. The pathological studies showed: parietal infiltrative ulcerative adenocarcinoma with venous tumoral suserous permeation.